50 Oscar nights : iconic stars & filmmakers on their career-defining wins - Karger, Dave (Running Press, an imprint of Hachette Book Group, Inc., 2024)
"Dave Karger--Turner Classic Movies on-air host, entertainment media darling, and the Oscars expert--offers a one-of-a-kind collection of original interviews with an A-list lineup of Oscar winners discussing the highs, lows, and never-before-told tales of Hollywood's most storied awards show"--